2014
DOI: 10.1016/j.toxrep.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage induced by hydroquinone can be prevented by fungal detoxification

Abstract: Hydroquinone is a benzene metabolite with a wide range of industrial applications, which has potential for widespread human exposure; however, the toxicity of hydroquinone on human cells remains unclear. The aims of this study are to investigate the cytotoxicity and genotoxicity of hydroquinone in human primary fibroblasts and human colon cancer cells (HCT116). Low doses of hydroquinone (227-454 μM) reduce the viability of fibroblasts and HCT116 cells, determined by resazurin conversion, and induce genotoxic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Hydroquinone (used for skin bleaching) is an aromatic organic compound, a type of phenol, leading to serious toxic effects on fauna and flora. Pereira et al (2014) reported that the hydroquinone drug has genotoxic property. The cytotoxicity of hydroquinone is caused by following the primarily oxidative damage methods to DNA (Enguita and Leitão 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroquinone (used for skin bleaching) is an aromatic organic compound, a type of phenol, leading to serious toxic effects on fauna and flora. Pereira et al (2014) reported that the hydroquinone drug has genotoxic property. The cytotoxicity of hydroquinone is caused by following the primarily oxidative damage methods to DNA (Enguita and Leitão 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The carbon dioxide evolved during aerobic respiration was quantitative adsorbed using droplets of NaOH (Carlo Erba Reagents, Milan, Italy) inside the sealed nozzle septum of the bottles. The pressure drop detected (every 100 min) in the bottle was proportional to the amount of oxygen used by fungi (Pereira et al, 2014;Schuchardt and Kruse, 2009;Willcock and Magan, 2001). …”
Section: Fungal Respirometric Analysismentioning
confidence: 99%
“…Due to its high toxicity and low degradability, HQ enhances the risk of environmental pollution. Unfortunately, exposure to HQ may cause skin inflammation, headache, edema, collapse, nausea, and eventually death because of failure of the respiratory system in humans. Therefore, developing a reliable analytical method is essential or necessary, which is facing all kinds of challenges. , …”
Section: Introductionmentioning
confidence: 99%